2003
DOI: 10.1104/pp.102.018762
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis haiku Mutants Reveal New Controls of Seed Size by Endosperm

Abstract: In flowering plants, maternal seed integument encloses the embryo and the endosperm, which are both derived from double fertilization. Although the development of these three components must be coordinated, we have limited knowledge of mechanisms involved in such coordination. The endosperm may play a central role in these mechanisms as epigenetic modifications of endosperm development, via imbalance of dosage between maternal and paternal genomes, affecting both the embryo and the integument. To identify targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
236
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(244 citation statements)
references
References 48 publications
7
236
0
1
Order By: Relevance
“…VQ14/HAIKU1 (IKU1) regulates the expression of MINISEED3 (MINI3; encoding a WRKY transcription factor) and IKU2 (encoding a Leu-rich repeat kinase), which are important for seed development (Garcia et al, 2003;Luo et al, 2005). The finding that the recessive vq14/iku1 mutant displays a smallseed phenotype indicates that VQ14 positively regulates endosperm growth and seed development.…”
Section: Vq Proteins In Plant Growth and Developmentmentioning
confidence: 99%
“…VQ14/HAIKU1 (IKU1) regulates the expression of MINISEED3 (MINI3; encoding a WRKY transcription factor) and IKU2 (encoding a Leu-rich repeat kinase), which are important for seed development (Garcia et al, 2003;Luo et al, 2005). The finding that the recessive vq14/iku1 mutant displays a smallseed phenotype indicates that VQ14 positively regulates endosperm growth and seed development.…”
Section: Vq Proteins In Plant Growth and Developmentmentioning
confidence: 99%
“…Since the pollen-parent in our hybrid crosses was wild-type A. arenosa, only haploinsufficiency, additive, or maternal effects could be observed. Because of the effect of hybridity on maternal seed coat and genes involved in the flavonoid pathway, we included in the analysis the maternally expressed factor TRANS-PARENT TESTA GLABRA2 (TTG2) (Johnson et al, 2002;Garcia et al, 2005), which also affects interploidy hybrid lethality (Dilkes et al, 2008), and IKU2 because of its relationship to IKU1 and endosperm development (Garcia et al, 2003(Garcia et al, , 2005. The genetic backgrounds of these mutants, Col-0 and Landsberg erecta-0 (Ler-0), influence percentage of live seed.…”
Section: Aberrant Expression Of Endosperm-localized Transcription Facmentioning
confidence: 99%
“…No experimental data have yet been obtained for the role of the nucellus, but recent advances have demonstrated that interplay between endosperm and seed integument growth is essential for seed size determination in Arabidopsis (Figure 2). Mutations in the HAIKU (IKU) genes decrease endosperm size and eventually embryo and seed size [23]. The HAIKU genes IKU2 and MINISEED3 (MINI3) encode a leucine-rich-repeat kinase and a WRKY transcription factor, respectively [24].…”
Section: Co-ordination Of Growth Between the Different Seed Componentsmentioning
confidence: 99%